Characterization of the Dynamic Imbibition Displacement Mechanism in Tight Sandstone Reservoirs Using the NMR Technique. (16th December 2020) - Dou, Liangbin; Yang, Min; Gao, Hui; Jiang, Dongxing; Liu, Chenglu
Abstract : An experimental technique is developed to investigate the dynamic imbibition displacement mechanism in tight sandstone formations of the Yanchang group of the Ordos basin. By combining the dynamic imbibition core flooding experiments and NMR technique, the effects of the injection volume and rate on displacement efficiency are investigated. Moreover, the displacement efficiency of dynamic imbibition is compared with that of static imbibition. This study gains insights into the micromechanisms of dynamic imbibition in tight sandstone formations. It is found that the relative displacement efficiency of dynamic imbibition increases with the increase of injection volume. But the increment amplitude decreases with the increase of injection volume. With the same injection volume, the core displacement efficiency of dynamic imbibition with high permeability is obviously improved. However, the core displacement efficiency decreases rapidly with the increase of injection volume. Optimal injection volumes are recommended for tight sandstone formations with different permeabilities. With the increase of the displacement rate, the core displacement efficiency of dynamic imbibition shows a trend of first rising and then declining. There exists an optimal displacement rate in dynamic imbibition displacement, and the optimal displacement rate almost linearly increases with the increase of core permeability. The static imbibition displacement efficiency increases with the increase of soaking time, but the increment amplitude slows down obviously. The displacement efficiency of static imbibition in small pores is higher than that of dynamic imbibition. The displacement efficiency of dynamic imbibition in large pores or microcracks is significantly higher than that of static imbibition. This study provides theoretical support for the optimization and improvement of the waterflooding recovery process in tight sandstone reservoirs.